Mahar Dalam Pernikahan Dan Dampaknya Terhadap Keharmonisan Dalam Rumah Tangga (Analisis Fenomenologis Terhadap Problem Pernikahan di Masyarakat Jawa) - Muhammad Aniq Yasrony (JATIJAJAR LAW REVIEW, 2022)
This research discussed about dowry in the marriage and its implication to the household’s harmony (phenomenological analysis of Surabaya people). it was aimed to analyze both the dowry’s substation in the marriage and its implication of giving dowry to the women whether it could create a harmonic family or not. It was conducted on three different clusters, they are abangan, santri, and priyayi.This was an empirical law research. The data was collected by interview the respondents using phenomenological approach based on the division of clusters, they are abangan, santri, and priyayi. Then, the data was analyzed and described qualitatively by transformative critical thinking. By this research, it was found that abangan, santri, and priyayi cluster had the different way to define about dowry in the marriage. Abangan clusters said that dowry was about the men’ loyalty and the acceptance of women without any reasons. Moreover, santri cluster declared that dowry was about men’ seriousness in a relationship and readiness to build a family together. This two clusters justified that there was no relationship between the existence of dowry and the harmonic family after marriage. On the other hand, priyayi cluster stated that dowry was the very important part of giving from the men to the women in the marriage. This cluster also claimed that there was a correlation about dowry and the felicitous of a family